Improving CFD prediction of drag on Paralympic tandem athletes: influence of grid resolution and turbulence model - Mannion, P.; Toparlar, Y.; Blocken, B.; Hajdukiewicz, M.; Andrianne, T.; Clifford, E. (Sports Engineering, 2018)
Tandem cycling enables visually impaired athletes to compete in cycling in the Paralympics. Tandem aerodynamics can be analysed by track measurements, wind-tunnel experiments and numerical simulations with computational fluid dynamics (CFD). However, the proximity of the pilot (front) and the stoker (rear) and the associated strong aerodynamic interactions between both athletes present substantial challenges for CFD simulations, the results of which can be very sensitive to computational parameters such as grid topology and turbulence model. To the best of our knowledge, this paper presents the first CFD and wind-tunnel investigation on tandem cycling aerodynamics. The study analyses the influence of the CFD grid topology and the turbulence model on the aerodynamic forces on pilot and stoker and compares the results with wind-tunnel measurements. It is shown that certain combinations of grid topology and turbulence model give trends that are opposite to those shown by other combinations. Indeed, some combinations provide counter-intuitive drag outcomes with the stoker experiencing a drag force up to 28% greater than the pilot. Furthermore, the application of a blockage correction for two athlete bodies in close proximity is investigated. Based on a large number of CFD simulations and validation with wind-tunnel measurements, this paper provides guidelines for the accurate CFD simulation of tandem aerodynamics.